Establishment of an in vitro cell line experimental system for the study of inhalational anesthetic mechanisms. (4th May 2016) - Nagamoto, Seiji; Iijima, Norio; Ishii, Hirotaka; Takumi, Ken; Higo, Shimpei; Aikawa, Satoko; Anzai, Megumi; Matsuo, Izumi; Nakagawa, Shinji; Takashima, Naoyuki; Shigeyoshi, Yasufumi; Sakamoto, Atsuhiro; et al.
Highlights: Two cell lines which stably express mPer2-dLuc were established. An experimental system to examine anesthetic response in vitro was developed. The system successfully applied anesthetics to cell cultures during incubation. The response was found in differentiated GT1-7:6D3 cells, but not in growing cells. Differentiated RS182 and N14.5:4B8.1 cells did not exhibit the response. Abstract: General anesthesia affects the expression of clock genes in various organs. Expression of Per2, a core component of the circadian clock, is markedly and reversibly suppressed by sevoflurane in the suprachiasmatic nucleus (SCN), and is considered to be a biochemical marker of anesthetic effect in the brain. The SCN contains various types of neurons, and this complexity makes it difficult to investigate the molecular mechanisms of anesthesia. Here, we established an in vitro experimental system using a cell line to investigate the mechanisms underlying anesthetic action. Development of the system comprised two steps: first, we developed a system for application of inhalational anesthetics and incubation; next, we established cultures of anesthetic-responsive cells expressing mPer2 promoter -dLuc . GT1-7 cells, derived from the mouse hypothalamus, responded to sevoflurane by reversibly decreasing mPer2 -promoter-driven bioluminescence. Interestingly, the suppression of bioluminescence was found only in the serum-starved GT1-7 cells, which showed neuron-like morphology, but not in growing cells, suggesting that neuron-like characteristics are required for anesthetic effects in GT1-7 cells.